The Influence of Job Characteristics and Job Satisfaction on Employee Performance in Plantation Companies - Raihan, Ahmad; Agustian, Wiwin; Septayuda, Irwan (International Journal of Finance Research, 2024)
This research, employing a unique quantitative method, seeks to ascertain the influence of job characteristics and job satisfaction on employee performance in plantation companies. The data was collected through a comprehensive questionnaire distribution process. The sampling technique used was saturated sampling, ensuring the inclusion of all population members as samples. The data analysis techniques included reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, coefficient of determination test, hypothesis test (t-test), and simultaneous test (F test). The results of this research underscore the positive and significant effect of job characteristics and job satisfaction on employee job performance